Medicine Adherence and Associated Factors in Immigrants and Refugees: A Systematic Review - Damini Patel; Zahraa Jalal; Ping Guo (International Journal of Clinical Practice)
Medicine nonadherence is a major contributing factor to morbidity and mortality. Almost half of the chronically ill patients are nonadherent to their medication. Vulnerable groups like immigrants and refugees are at a higher risk of poor medication adherence. This study aims to determine the rate of medicine adherence and the factors associated with medicine nonadherence in a population of immigrants and refugees. A protocol-led (PROSPERO ID: CRD42021285419) systematic review was conducted by searching PubMed, Medline, Embase, Scopus, CINAHL, and Cochrane Library for studies published between 1st January 2000 and 4th November 2021. PRISMA guidelines were followed. The NIH quality assessment tool and CASP checklist were used to quality assess the papers. Data were searched, screened, and extracted. Extracted data were tabulated for descriptive and narrative analyses. 15 studies were conducted across six countries including participants with various medical conditions. The rate of medicine adherence reported ranged from 10.1% to 74.5%. Higher rates of nonadherence were observed in immigrants and refugees compared to migrant and native groups. Socio-economic factors, including language proficiency, level of education, and financial burden, and patient-related factors involving cultural behaviours and beliefs were common themes for nonadherence among immigrants and refugees. Further research is required to address the effect of nonadherence on clinical outcomes. Studies should focus on using a consistent definition of adherence and the same objective methods to measure rates of adherence to allow for meta-analysis of data and definitive results. Healthcare professionals (HCPs) are recommended to target interventions at improving adherence and reducing modifiable risk factors in immigrants and refugees, thus reducing health disparities among the population.